An assessment of the Edu-Tourism @UKMlivinglab Package test-run - Farah Shafawati Mohd-Taib,; Mohd Shazrul Fazry Sa’ariwijaya,; Nur Amelia Abas,; Raja Farzarul Hanim Raja Azmy,; Norela Sulaiman,; Haja Maideen Kadeer Maideen,; Mohamad Ruzi Abdul Rahman,; Asamuddin Abu Hasan,; Muhammad Shafiq Ruslan,; Mohd Afiq Aizat Juhairi,; Liew, Ju Neng; Azman Sulaiman,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2020)
An edu-tourism package has been developed which encompassed nature-based tourism at the natural living laboratories of Universiti Kebangsaan Malaysia (UKM). With the theme “From Mountain to the Reef”, this package comprised of tourism module based on the natural ecosystem of respective living laboratory of UKM, involving four natural habitats; highland, lowland, freshwater and marine. In order to assess the effectiveness of the module, we have distributed a set of questionnaire to the participants during the test-run, involving all the living lab facilities. This pilot study involved 13 participants from various academic background, enrolling either as undergraduates or postgraduates study at UKM. The result of the questionnaire showed positive feedbacks from the participants for both the learning modules, as well as the overall program. There were however, several room of improvements to be made from the feedbacks. This package is expected to be marketed locally and internationally for students and public, in order to generate revenue for the university and stakeholders. This project has proven to be research translated to the community through the empowering of the human capitals (staffs and local community) through the living laboratory facilities.